The liberalization in the EC's telecommunications sector and its effects - Christine Borrmann (Intereconomics, 1993)
The telecommunications sector is a powerfully growing market which is expected to play a key role in the EC of the future. This article offers a survey of the liberalization measures envisaged in this formerly heavily protected sector followed by an analysis of their economic effects on both EC member states and third countries.
Keywords: 330